The Soccer Coaching Handbook - Bidzinski, Martin (Marlborough The Crowood Press, 2000)
This manual is full of detailed ideas, theories, and suggestions; it will be of real value for anyone actively coaching or seriously interested in improving their standard of soccer coaching whether from school leagues or professional division clubs. The author has created a unique training course concentrating on close control and ball movement$1 (Bthe keys to touch play. Included is a detailed week by week fitness program and structured training schedule. Clear diagrams accompany each new game plan and are designed to be reproduced on the training field. Coaching exercises covered include speeding up reaction times; one-touch play; three-point defence systems; attacking runs from deep positions; and improvising in set pieces.s
Include Illustrations and Index.
Keywords: Soccer--Coaching -- Great Britain -- Soccer